Can Vitamin D Supplementation Improve the Severity of Congestive Heart Failure?. Issue 4 (21st March 2013) - Amin, Ahmad; Minaee, Shima; Chitsazan, Mitra; Naderi, Nassim; Taghavi, Sepideh; Ardeshiri, Maryam
Abstract : The aim of the present study was to investigate whether vitamin D supplementation could improve biochemical findings and functional capacity of patients with heart failure (HF). One hundred patients with New York Heart Association (NYHA) class I through III HF were included in this prospective study and their 25‐hydroxyvitamin D levels were evaluated. Only 6% of the participants had a sufficient serum concentration of 25(OH) D >30 nmol/L. Patients with insufficient or deficient serum levels of 25(OH) D (<30 ng/mL and <20 ng/mL, respectively) received oral vitamin D3 (cholecalciferol) for a total period of 4 months. Vitamin D supplementation increased mean serum concentration of 25(OH) D from 12.63±7.60 nmol/L to 54.49±18.01 nmol/L ( P <.001). After vitamin D supplementation, the serum level of pro‐brain natriuretic peptide markedly decreased ( P <.001). Cholecalciferol significantly decreased high‐sensitivity C‐reactive protein level ( P <.001). Restoration of serum 25(OH) D level was also associated with substantial improvement in NYHA class ( P <.001) and 6‐minute walk distance ( P <.001).